Comparison of Gyrus PKS™ PlasmaSpatula Versus Vectec™ Monopolar L-Hook During Colpotomy Step in Total Laparoscopic Hysterectomy in Terms of Vaginal Cuff Thermal Damage - Çimşir, Meral Tuğba; Yıldız, Muhammet Serhat; Günizi, Ceren (Cerrahpaşa Medical Journal, 2022)
Objective: Thermal injury is a complication that can develop during laparoscopic hysterectomy. The ureter, which is located close to the surgical margin, may be damaged, especially due to the thermal effect created by the electrosurgical devices used in the colpotomy step. The aim of this study is to compare the vaginal cuff thermal injury caused by 2 different energy-based surgical devices used in the colpotomy step in total laparoscopic hysterectomy. Methods: The study included 55 patients who underwent laparoscopic hysterectomy. Patients were randomly assigned to the Bipolar Gyrus® PKS PlasmaSpatula (Gyrus-ACMI, Maple Grove, MA) cutting device group (n = 27) or the Monopolar L-Hook (VECTEC, Bioparc, Hauterive, France) cutting device group (n = 28), and colpotomy was performed using the assigned energy-based surgical device for each group. The removed uterus was examined by the same pathologist in the pathology department. During the colpotomy stage, the thermally damaged area was measured and photographed in millimeters from the application point of the electrosurgical device at the cervix–vaginal border. The extent of lateral thermal damage was measured in width using a light microscope from the point of instrument application to the margin of unchanged nearby tissue. Results: Thermal damage was significantly greater in the Monopolar L-Hook group than in the Bipolar Gyrus ® PKS PlasmaSpatula cutting device group (8.1 mm [range 6.6-9.1 mm] vs. 4.7 mm [range 4.1-5.6 mm], P = .000). However, Bipolar Gyrus ® PKS PlasmaSpatula provided a better surgical field as it did not produce excessive smoke and caused less thermal damage. The colpotomy time, cuff closure time, total operative time, blood loss, and cuff cellulite were similar between the 2 groups. Conclusion: Bipolar Gyrus ® PKS PlasmaSpatula caused less lateral thermal damage and provided a better non-smoked surgical view compared to the Monopolar L-Hook cutting device. Cite this article as: Çimşir MT, Yıldız MS, Günizi C. Comparison of Gyrus PKS™ plasmaspatula versus vectec™ monopolar L-hook during colpotomy step in total laparoscopic hysterectomy in terms of vaginal cuff thermal damage. Cerrahpaşa Med J. 2022;46(1):66-70.